The Differences of Omphalitis Events Between Closed and Open Cord Care with Dry Gauze - Shinta Novelia; Yenny Aulya; Syallom Try Utami (Nursing and Health Sciences Journal (NHSJ), 2023)
The high morbidity and mortality rate of newborns throughout the world is caused by infection. Southeast Asia estimated that there were 220,017 infant deaths due to unclean umbilical cord care. Umbilical cord care is very important, especially for mothers giving birth because mothers are more aware of the baby's development every day. This study aimed to determine the difference between the incidence of omphalitis between dry gauze closed umbilical cord care and open umbilical cord care in Midwife S. L. Clinic and Teratai Clinic, East Jakarta in 2020. This research is quantitative research with an analytical survey method with a cross-sectional approach. The sample in this study was 67 people. The sampling technique is total sampling. The research instrument consisted of secondary data and observation sheets. Chi-square test results there were differences in the incidence of infection between the treatment of dry gauze closed umbilical cord with open umbilical cord care where (ρ=0.000). There was a difference between the occurrence of infection between the treatment of the cord that is closed with dry gauze and open. Post-partum women need to increase their knowledge about umbilical cord care both with the open umbilical cord care method so that they can apply the open umbilical cord care method and reduce the incidence of omphalitis in infants.